Manuscripts in V. A. Zhukovsky’s collection associated with the name of Cesarevich Alexander Nikolayevich - V. A. Esipova (Библиосфера, 2017)
The article considers five manuscripts related to the name of Cesarevich Alexander Nikolaevich, which nowadays are stored in V.A. Zhukovsky’s collection of Tomsk State University Research Library (Tomsk, Russia). It gives brief manuscripts descriptions, as well as information about their authors; describes some aspects of Cesarevich and his tutor relationships reflected in the manuscripts stories. One manuscript belonged to Cesarevich is devoted to describing the composition and administrative structure of the Russian Empire. Its content and presentation character correspond to educational principles preached by Zhukovsky: «It is better less, but well learnt, than much, but poorly learnt». Another manuscript «Brief review of the Comissariat in historical and statistical aspects» is devoted to the history of the Comissariat Department of the Military Ministry. Probably, its author was S. Shipov, who expected to present the manuscript to Cesarevich; the dedication to hum is seen at the beginning of the text. However, for different reasons, the presentation did not take place, and the manuscript remained in Zhukovsky’s library. One more manuscript was also intended for presenting to Cesarevich. It is «The feeling of a Russian on the return of the adored Sovereign heir from a voyage across Russia». Two more manuscripts from Zhukovsky’s library were written with the same handwriting: «The Sacred Tribute of a Russian or Patriotic Offering» and «A Lost Mortgage or Half an Hour of Testing». The author hypothizes that all three manuscripts are associated with the name of a serf self-taught poet S. Sibiryakov, whose fate was actively paticipated by Zhukovsky. Thus, three manuscripts from Zhukovsky’s library can be viewed as related to Cesarevich Alexander Nikolaevich. They allowed imagining various aspects of the relationships between the Cesarevich and his tutor. One of them is the education of attitudes toward charity as a civil act. It is also evident that the books of the Romanovs dynasty representatives could be deposited not only in their personal or palace libraries, but some copies could be included in book collections of persons, close to the Tsar family.